The millipede genus Pandirodesmus Silvestri, 1932 in Trinidad and Tobago, Caribbean, with the description of P. jaggernauthi sp. nov. from Trinidad (Diplopoda, Polydesmida, Chelodesmidae, Pandirodesmini) - Vandenspiegel, Didier; Golovatch, Sergei I.; Rutherford, Mike G. (Zootaxa, 2022)
During several collecting surveys for terrestrial micro-molluscs across Trinidad and Tobago, millipedes of the genus Pandirodesmus were taken by MR on both islands. Samples of P. rutherfordi Shelley & Smith, 2015, from Tobago, were recovered in addition to those containing a new species from Trinidad: Pandirodesmus jaggernauthi sp. nov. Additional records, illustrations, and descriptive notes are given for P. rutherfordi. A key is presented to all three species of the genus, and their distributions are mapped.